The Little Data Book on Information and Communication Technology 2018 - World Bank Group; International Telecommunication Union (Washington, DC: World Bank, 2019)
Since the late 1990s access to information and communication technologies (ICTs) has seen tremendous growth—driven primarily by the wireless technologies and liberalization of telecommunications markets. Mobile communications have evolved from simple voice and text services to diversified innovative applications and mobile broadband Internet. In 2016, there were more than 7.3 billion mobile-cellular subscriptions worldwide. Globally, 3.5 billion people were using the Internet, of which 2.5 billion were from developing countries. Mobile-broadband subscriptions have risen constantly to reach 3.6 billion, while the number of fixed-broadband subscriptions reached more than 84 million during the same period. The impacts of ICTs cross all sectors. Research has shown that investment in information and communication technologies is associated with such economic benefits as higher productivity, lower costs, new economic opportunities, job creation, innovation, and increased trade. ICTs also help provide better services in health and education, and strengthen social cohesion. The Little Data Book on Information and Communication Technology 2018 illustrates the progress of this revolution for 217 economies around the world. It provides comparable statistics on the sector for 2010 and 2016 across a range of indicators, enabling readers to readily compare economies. This book includes indicators covering the economic and social context, the structure of the information and communication technology sector, sector efficiency and capacity, and sector performance related to access, usage, quality, affordability, trade, and applications. The glossary contains definitions of the terms used in the tables.